The Impact of Credit Management and Liquidity on financial performance of Deposit Taking Savings and Credit Cooperatives In Kenya - Kahuthu, David G.; Muturi, Willy; Kiweu, Joséphat M. (Research Journal of Finance and Accounting, 2015)
Savings and credit cooperative Societies (SACCOs) have granted loans over the years without concentrating on the quality of loans in their portfolios and hence maintained key assets in their books that would not be accounted for. Similarly they have provided cash to clients without any purposive determination of cash levels. The study therefore sought to ascertain if liquidity and credit management played important roles in determination of revenues of deposit taking SACCOs in Kenya. To ascertain factually if the two variables had any role, the study chose to examine the coefficients of Beta before statutory management which was implemented in 2010 and the coefficients of Betas after 2010. The vigorous processes of research exercise were undertaken with findings, conclusions and recommendations being made on the basis of analytical manipulation of data. The study findings were that liquidity and credit management had great impact on SACCOs financial performance especially if managed prudently and strengthened by the legal framework as a moderating variable. The study recommends that SACCOs should continuously formulate proper loan products and maintain adequate cash balances for profitability and financial stability of the SACCO. They should also develop key policies on staff recruitment and retention, liquidity and loan provisioning to enable SACCOs increase financial performance. This study will empower SACCOs with Knowledge on prudential credit and liquidity management guaranteeing sustainability and profitability while using own resources.
Keywords: SACCO